The North Atlantic genus Heteromesus (Crustacea: Isopoda: Asellota: Ischnomesidae) - Cunha, Marina R.; Wilson, George D.f. (Zootaxa, 2006)
Sixteen species of Heteromesus Richardson are reviewed, additional terms are introduced to account for special morphologies in the Ischnomesidae, the diagnosis of the genus is updated and a key to species is given. Twelve species, which have previously been recorded from the Atlantic Ocean, are redescribed and four new species are described, H. calcar, H. ctenobasius, H. inaffectus and H. oryktus. Heteromesus similis Richardson is illustrated for the first time and H. bifurcatus Menzies, H. dentatus Hansen, H. frigidus Hansen, H. greeni (Tattersall), H. granulatus Richardson, H. schmidtii Hansen, H. spinescens Richardson and H. spinosus (Beddard) are reillustrated from the type material. The morphological features and ecology of the genus are discussed. The specimens of the new species H. calcar and H. ctenobasius, collected from Lucky Strike (Mid-Atlantic Ridge), are the first record of Heteromesus from hydrothermal vent habitats. Finally, the biogeography of the genus is reviewed and confirms that Heteromesus is a deep-sea genus restricted primarily to the North Atlantic and Arctic Seas. Data on unpublished records of undescribed Heteromesus spp. allows us to predict a much more diverse composition of the genus and sets the southern limit of its distribution at around 23ºS in the Eastern South Atlantic off Africa (Walvis Bay).